“Theatre Phenomenology” and Ibsen’s The Master Builder - Johnston, Daniel (Nordic Theatre Studies, 2019)
How might an actor find inspiration from philosophy to build a world on stage? This article examines how phenomenology can offer a framework for creating performance and a vocabulary for action in rehearsal. Taking Henrik Ibsen’s The Master Builder as a case-study, a number of exercises and approaches are suggested for exploring the text while drawing on Martin Heidegger’s lecture, “Building, Dwelling, Thinking” which ponders the nature of “building”. Far from merely “constructing” an environment, essentially, building is “dwelling”. As the characters in Ibsen’s drama go about their dwelling, actors must build a world